ANALISA SISTEM PEMELIHARAAN DAN PERBAIKAN ALAT ELEKTROCARDIOGRAPH - Siregar, Adlin Khairi; Sijabat, Salomo; Priyulida, Fitria; Dabukke, Hotromasari (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Electrocardiograph is a tool that can display a graph of the electrical signal of the human heart that shows the process of the occurrence of a heartbeat. Through this tool it can be known whether a person's heart rate is normal or not. The method used in this study is qualitative and descriptive. preventive maintenance both from outside and inside the tool and aims to find out the maintenance of the el ectrocardiograph tool this maintenance function is running well, then the quality of the medical equipment used will be good too. From the results of the maintenance and testing of the electrocardiograph that was carried out at the Teaching Hospital of the University of North Sumatra, Medan. The maintenance of the electrocardiograph was carried out by internal calibration with measurements of 30,60,120,240.and by looking at the value of the graph whether it was still curly or not.The results of this study indicate that in practice, the system of maintenance cannot run as it should, due to the limited number of technicians, lack of training, costs, and maintenance procedures that are not in accordance with the planning, operation, and supervision procedures that are not carried out properly.